2021
DOI: 10.1021/acsami.1c12564
|View full text |Cite
|
Sign up to set email alerts
|

Visible to Short-Wave Infrared Photodetectors Based on ZrGeTe4 van der Waals Materials

Abstract: The self-terminated, layered structure of van der Waals materials introduces fundamental advantages for infrared (IR) optoelectronic devices. These are mainly associated with the potential for low noise while maintaining high internal quantum efficiency when reducing IR absorber thicknesses. In this study, we introduce a new van der Waals material candidate, zirconium germanium telluride (ZrGeTe 4 ), to a growing family of promising IR van der Waals materials. We find the bulk form ZrGeTe 4 has an indirect ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 56 publications
(81 reference statements)
0
10
0
Order By: Relevance
“…The performance of PDs is measured under illumination with a calibrated 600 °C blackbody of a band radiance around 707.09 W m –2 sr –1 , corresponding to 2.22 mW cm –2 . The responsivity as an important performance indicator is obtained by dividing the measured photocurrent by a radiated power incident on the photosensitive region of the detector, as shown in Equation S2. ,,,, The responsivity of the ZnO/HgTe/Ag 2 Te reaches 1.85 A W –1 at the bias voltage of 2 V, which is much higher than that of the photodiodes without ZnO and the representative detectors of literature, as seen in Figure e and the performance comparison for recent QD-based PDs of Table S3. The specific detectivity given by eq S3 is a measure of the signal-to-noise ratio for a given incident power and normalized to the detector area with units of or Jones. ,,,,, The detectivity of the ZnO/HgTe/Ag 2 Te photodiodes is as high as 4.86 × 10 10 Jones at 2 V, which is a fourfold improvement compared with the HgTe/Ag 2 Te stack (Figure e).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The performance of PDs is measured under illumination with a calibrated 600 °C blackbody of a band radiance around 707.09 W m –2 sr –1 , corresponding to 2.22 mW cm –2 . The responsivity as an important performance indicator is obtained by dividing the measured photocurrent by a radiated power incident on the photosensitive region of the detector, as shown in Equation S2. ,,,, The responsivity of the ZnO/HgTe/Ag 2 Te reaches 1.85 A W –1 at the bias voltage of 2 V, which is much higher than that of the photodiodes without ZnO and the representative detectors of literature, as seen in Figure e and the performance comparison for recent QD-based PDs of Table S3. The specific detectivity given by eq S3 is a measure of the signal-to-noise ratio for a given incident power and normalized to the detector area with units of or Jones. ,,,,, The detectivity of the ZnO/HgTe/Ag 2 Te photodiodes is as high as 4.86 × 10 10 Jones at 2 V, which is a fourfold improvement compared with the HgTe/Ag 2 Te stack (Figure e).…”
Section: Resultsmentioning
confidence: 99%
“…34,35,41,43,44,57 The detectivity of the ZnO/HgTe/Ag 2 Te photodiodes is as high as 4.86 × 10 10 Jones at 2 V, which is a fourfold improvement compared with the HgTe/Ag 2 Te stack (Figure 3e). Not only that, the ZnO/HgTe/Ag 2 Te PV PDs demonstrate competitive detectivity among recent CQD-based PDs, [47][48][49][50][51][52][53][54][55][56]58,59 as summarized in Table S3. Besides responsivity and detectivity, the linear dynamic range (LDR) defined as the linear light intensity dependence of the photocurrent 60 for the ZnO/HgTe/Ag 2 Te PD is around 93 dB, as shown in Figure S8.…”
Section: ■ Introductionmentioning
confidence: 99%
“…© 2021 Wiley-VCH GmbH ZrGeTe 4 , [155] and Bi 2 O 2 Se [19] ) have been used to explore highperformance IR photoconductors. For example, Lai et al demonstrated a TaIrTe 4 -based LWIR photoconductor, which realized high speed and highly anisotropic photoresponse over a broad spectral range from 0.532 to 10.6 µm.…”
Section: (17 Of 38)mentioning
confidence: 99%
“…In addition to 2D TMD semiconductors, some 2D compound semiconductors (e.g., SnTe, [ 151 ] GeAs, [ 152 ] NbS 3 , [ 153 ] TaIrTe 4 , [ 154 ] ZrGeTe 4 , [ 155 ] and Bi 2 O 2 Se [ 19 ] ) have been used to explore high‐performance IR photoconductors. For example, Lai et al.…”
Section: Ir Photoconductors Based On 2d Materialsmentioning
confidence: 99%
“…Similarly, two-dimensional (2D), or van der Waals, materials can be transferred onto arbitrary substrates and easily stacked in vertical heterostructures due to their out-of-plane van der Waals bonding . Furthermore, the low volume-dependent thermal noise and thickness-tunable bandgap as well as the high quantum efficiencies and carrier mobilities commonly exhibited in 2D materials are all advantageous in IR photodetection. , To date, several 2D materials have been incorporated as absorbers in IR sensing systems including graphene, , Te, , PtSe 2 , MoTe 2 , , ZrGeTe 4 , , black phosphorus (bP), and black phosphorus arsenic (bPAs). , Some of these 2D materials (e.g., graphene and Te) and their heterocontact materials (e.g., MoS 2 ) have already been demonstrated in wafer-scale applications, ,, suggesting others could also be scaled up with further development. Among the various 2D IR materials, bP has drawn significant attention as an emerging material for midwave IR (MWIR λ = 3 to 5 μm) applications. ,, At thicknesses above 10 layers, bP exhibits its bulk bandgap of ∼0.31 eV, which increases through the SWIR and visible region for thinner layers. , Black phosphorus also exhibits high mobilities and strong optical anisotropy, enabling devices with short response times and polarization sensitivity, respectively.…”
Section: Introductionmentioning
confidence: 99%